Pervaporation of isopropanol-water mixture using poly(vinyl) alcohol-zsm-5 membranes - Chong, Woon Chan; Mohd Nawawi, Mohd Ghazali; Sadikin, Aziatul Niza (Penerbit UTM Press, 2008)
The pervaporation separation of isopropanol-water mixture was carried out using poly(vinyl) alcohol (PVA) membrane incorporated with 0.2 wt% ZSM-5 zeolite. The manipulated variables were feed temperature and feed concentration. Initially, 5 wt% of PVA powder was dissolved in distilled water at 98 Â°C. The solution was stirred using magnetic stirrer for 1 hour to produce a homogenous solution. It was then cooled to room temperature before added with the zeolite. The PVA-zeolite solution was stirred for 24 hours at room temperature before it was casted on a porous support. The support layers were produced through phase inversion using casting solution of 12 wt% polysulphone, 11 wt% cellusolve and 77 wt% N,N-dimetil formamide (DMF). Finally, the modified composite membranes were produced by casting the PVA- zeolite solution on the porous polysulphone support layers. Pervaporation tests were conducted using SOLTEQ Pervaporation Bench Test Unit (Model: TR 12). The results showed the increase of water concentration in the feed and operating temperature, resulted in higher flux and lower selectivity. ZSM-5 filled PVA membrane showed potential as a separation medium for the pervaporation separation of isopropanol-water mixtures.